TOPICAL ISSUES OF TOBACCO PRODUCTS’ ILLICIT TRADE - Naglis, Valdis (Administrative and Criminal Justice, 2019)
Criminal offences related to the illicit movement of tobacco products are among the most complex forms of crime affecting not only the state but also the economic processes in it. Via the development of modern technologies, it becomes more wide-spread, latent, and more influential as a result of international communication and transnational activities. Recently, the topicality has increased concerned with the illicit production of tobacco products, people who engage in this type of illegal activities get caught more and more frequently. The aim of the research: to study the norms of the Criminal Law article regarding the illegal circulation of tobacco products, to express an opinion on the improvement necessity of the Criminal Law norm, to find possible identification of the most significant problems related to it, as well as to make proposals for a more effective solution of this issue.